Genetic and Non-Genetic Factors Affecting Performance Traits in Crossbred Dairy Cattle in an Organised Farm - Kaur, Simran; Ghosh, Ashis Kumar; Kumar, Devendra; Barwal, Ravinder Singh; Shahi, Bijendra Narayan; Kumar, Sunil (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Data on performance records of 529 crossbred animals available from organised herd of Instructional dairy farm of Govind Ballabh Pant University of Agriculture and Technology, Pantnagar spread over a period of 30 years (1990-2019) were analysed to determine the effect of several genetic and non-genetic factors on performance traits viz. age at first calving (AFC), first service period (FSP), first dry period (FDP), first calving interval (FCI), first lactation period (FLP), first lactation milk yield (FLMY), first lactation 305 days milk yield (FL305DMY), first lactation peak yield (FLPY) and first lactation days to attain peak yield (FLDAPY). The random effect of sire had statistically significant (P< 0.01) effect on AFC, FLMY, FL305DMY and FLPY. Genetic group had statistically significant effect on FSP (P<0.05), FL305DMY (P<0.01) and FLDAPY (P<0.05). Season of calving significantly (P<0.05) affected FL305DMY and FLDAPY. The significant differences of period of calving were observed on AFC (P<0.01), FSP (P<0.05), FLP (P<0.01), FLMY (P< 0.01), FL305DMY (P<0.01) and FLDAPY (P<0.01). Variability in the traits due to various factors might be attributed to the differences in genetic groups and management practices. Therefore, satisfactory management and appropriate genetic improvement strategies would result in ameliorating the performance of animals.